Pendidikan Holistik Dalam Kitab Ta’limul Muta’allim Perspektif Zarnuji - Nurhayati, Dewi; Afifah, Muruatul; El-faradis, Fayruzah (Proceedings of International Conference on Muslim Society and Thought, 2024)
Education in fact, get the challenge that in line with the intellectual advanced and development era. Commonly, the society defined and understand the education as it was. Education only depends on knowledges transformation classically and formally. In reality education is very complex that requires various solutions and implementations of its unique and complexity. Thus, visioner education with the new concept hopefully can cover and fulfill the life needs. The new concept thinking is required in order to support innovative education. This article describes the education concept that it’s existence trapped to formality concept and empty-knowledge transformation only, referred to one understanding only, while human beings live with all unique and complexity in all aspects of life. Besides of that, human being with their complexity have instinct and needs that in line with knowledge instinct thus could be solutions of every problems. This research method uses qualitative research methods with documentation data collection methods, in the form of literature studies from the Zarnuji books This article offer one concept that expected to solve that problem through the holistic education in Islam on Zarnuji’s perspective.